STUDY OF ROLLING CONTACT OF A CYLINDER ON A ROUGH SURFACE WITH FINITE ELEMENT ANALYSIS - Rifky Ismail; M. Tauviqirrahman; . Jamari; D.J. Schipper (Prosiding SNST Fakultas Teknik, 2010)
This work presents a simulation of 2D rolling contact on a rough surface using a finite element analysis (FEA). The finite element software, ABAQUS, is used for simulating the rigid cylinder rolls over on a rough surface with different applied loads. The rough surface is considered to be elastic-perfectly plastic aluminum with strain hardening. The pure rolling and frictionless contact is assumed in the cylinder movement on a certain linear distance. The applied load is modeled as three different interferences, which results deformations and stress distributions. The static contact between a rigid indenter on a rough surface is used to validate the result by comparing the present results and the previous research results. The resulted elastic-plastic deformation and von Mises stress distribution in the simulation is reported. The increase of the applied load results the larger the deformation of the asperity on the rough surface. It also takes effect on the von Mises stress distribution. The plastic deformation area on the top of the rough surface asperity become wider as the load is increase. The deformation and stress distribution in the simulation describes the phenomenon where the engineering surface is deformed due to the rolling contact. Keywords: rolling contact, rigid cylinder, rough surface, finite element